Kajian komparatif tentang korosi pada Point-Absorber dan Pelamis dengan analisis kontekstual di Indonesia - Salsabila, Vedora Aprillia; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
Global energy demand is rising while fossil fuel reserves are declining, making renewable energy a critical solution. Ocean wave energy, with a potential of around 2 TW, is a promising alternative, yet the corrosive marine environment challenges the durability of Wave Energy Converters (WEC). This study uses a Systematic Literature Review (SLR) to compare the corrosion resistance of two WEC types, Point-Absorber and Pelamis, and assess their suitability for Indonesia. Results show that Point-Absorbers are prone to corrosion fatigue, whereas Pelamis devices are more vulnerable to crevice corrosion. Appropriate material selection, such as 316L stainless steel or carbon fiber composites, along with corrosion protection, is essential, and site-specific factors wave potential, grid proximity, and environmental impact must be considered for sustainable WEC deployment.